2016
DOI: 10.1111/nph.14013
|View full text |Cite
|
Sign up to set email alerts
|

A multilayered regulatory mechanism for the autoinhibition and activation of a plant CCNBLRR resistance protein with an extra N‐terminal domain

Abstract: The tomato resistance protein Sw-5b differs from the classical coiled-coil nucleotide-binding leucine-rich repeat (CC-NB-LRR) resistance proteins by having an extra N-terminal domain (NTD). To understand how NTD, CC and NB-LRR regulate autoinhibition and activation of Sw-5b, we dissected the function(s) of each domain. When viral elicitor was absent, Sw-5b LRR suppressed the central NB-ARC to maintain autoinhibition of the NB-LRR segment. The CC and NTD domains independently and additively enhanced the autoinh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 52 publications
3
85
0
1
Order By: Relevance
“…This type of NLR protein is unique to wheat-related families and may reflect the existence of a specific NLR-mediated disease resistance mechanism in wheat relatives. Several NLR resistance proteins reported previously have additional domains, such as the Arabidopsis resistance protein RRS1, with a C-terminal WRKY domain; rice blast resistance protein RGA5, with a C-terminal RATX1 domain; tomato resistance protein Sw-5b has an extra N-terminal domain; and wheat stripe rust resistance proteins Yr5, Yr7 and YrSP, with N-terminal BED domains 7,15,18,19 . YrU1 is the first NLR protein reported with extra domains at both the N and C termini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of NLR protein is unique to wheat-related families and may reflect the existence of a specific NLR-mediated disease resistance mechanism in wheat relatives. Several NLR resistance proteins reported previously have additional domains, such as the Arabidopsis resistance protein RRS1, with a C-terminal WRKY domain; rice blast resistance protein RGA5, with a C-terminal RATX1 domain; tomato resistance protein Sw-5b has an extra N-terminal domain; and wheat stripe rust resistance proteins Yr5, Yr7 and YrSP, with N-terminal BED domains 7,15,18,19 . YrU1 is the first NLR protein reported with extra domains at both the N and C termini.…”
Section: Discussionmentioning
confidence: 99%
“…Several also have additional functional domains, which are hypothesised to act as integrated decoys. For instance, the Arabidopsis thaliana (Arabidopsis) resistance protein RRS1 has a C-terminal WRKY domain; the rice (Oryza sativa) resistance protein RGA5 has a C-terminal RATX1 domain; the wheat stripe rust resistance proteins Yr5, Yr7 and YrSP have an N-terminal BED domain; and the tomato resistance proteins Sw-5b and Prf have an extra N-terminal domain 7,[15][16][17][18] . Among these, the RATX1 domain of RGA5 directly binds to a Magnaporthe oryzae effector, and activates RGA4-mediated resistance and cell death upon recognition 17,19 .…”
mentioning
confidence: 99%
“…In consideration of their physical clusters in chromosomes, it seems an ancestral NL tandemly proliferated to increase the copy number. If the N-terminal domain and CC are essential for auto-inhibition of NLRs as found for Sw-5 in G6[8,6163], it is yet unclear how this ancestral NL achieved it without the two domains and was eventually selected by evolution. Although some attempted to elucidate their functions, more diverse studies will be required[64].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that Sw-5b recognizes a conserved 21amino-acid region in NSm (NSm 21 ) to provide a broad-spectrum resistance to the American type of tospoviruses (Zhu et al, 2017). We have also shown that the regulation of auto-inhibition and activation of Sw-5b, which contains the extended SD, is multilayered (Chen et al, 2016). However, the precise role of the Sw-5b SD in the recognition of the NSm effector and the exact mechanism by which the Sw-5b receptor is activated remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%